The potential for senotherapy as a novel approach to extend life quality in veterinary medicine - Williams, Zoë J.; Chow, Lyndah; Dow, Steven; Pezzanite, Lynn M. (Frontiers in Veterinary Science, 2024)
Cellular senescence, a condition where cells undergo arrest and can assume an inflammatory phenotype, has been associated with initiation and perpetuation of inflammation driving multiple disease processes in rodent models and humans. Senescent cells secrete inflammatory cytokines, proteins, and matrix metalloproteinases, termed the senescence associated secretory phenotype (SASP), which accelerates aging processes. In preclinical models, drug interventions termed 'senotherapeutics' selectively clear senescent cells and represent a promising strategy to prevent or treat multiple age-related conditions in humans and veterinary species. In this review, we summarize the current available literature describing in vitro evidence for senotheraputic activity, preclinical models of disease, ongoing human clinical trials, and potential clinical applications in veterinary medicine. These promising data to date provide further justification for future studies identifying the most active senotherapeutic combinations, dosages, and routes of administration for use in veterinary medicine.